A Systematic Survey of Physicians' Insights Into Lipohypertrophy - Shen, Min; Shi, Yun; Zheng, Shuai; Fan, Hongqi; Xu, Jingjing; Yang, Tao (Frontiers in Public Health, 2021)
Introduction: Physicians play key roles during diabetes management. The skin-related complications associated with insulin therapy are known as lipohypertrophy (LH), and it is important that physicians be aware of this condition. We designed a questionnaire to determine physician awareness, knowledge, and behaviors regarding LH in clinical practice. Research design and methods: A total of 499 questionnaires were completed by physicians in hospitals from 13 cities in Jiangsu Province, China. Results: Most physicians claimed to be aware of LH. Compared with physicians at tertiary hospitals, significantly fewer physicians at primary hospitals reported awareness of LH and its screening methods (P < 0.05). The proportion of resident physicians aware of LH was significantly lower than the proportion of senior physicians (P < 0.05). Physicians primarily believe that the failure to effectively rotate insulin injection sites and frequent needle reuse result in LH occurrence. The proportion of physicians who could identify all LH risk factors among the low-gross domestic product per capita (low-GDP) group was significantly higher than the proportion in the high-GDP group (50% vs. 29.2%, P = 0.000). Only 38.7% (193/499) of doctors could successfully identify all the hazards associated with LH, but more doctors in tertiary hospitals were able to do so compared to those in secondary and primary hospitals (P < 0.05). Compared with tertiary hospitals, the proportions of secondary and primary hospitals with management processes were significantly lower (P < 0.05). The proportion of doctors who educated patients regarding LH prevention and treatment in primary hospitals was markedly lower than in tertiary hospitals (P < 0.05). Conclusions: Overall, physicians have an inadequate understanding of LH, especially in primary hospitals. Increasing physician awareness of LH, establishing standardized diagnosis-treatment-care processes, and regularly screening and educating patients are urgent needs in primary hospitals.